Compression and reconstruction of extremely-high resolution holograms based on hologram-lightfield transforms - Gilles, Antonin; Gioia, Patrick (Applications of Digital Image Processing XLIII, 2020)
Holography is often considered as the most promising 3D visualization technique, creating virtual images indistinguishable from the real ones. However, one the main barrier to the adoption of holographic displays in wide 3D viewing systems is the very large amount of information contained in a hologram. Indeed, a hologram with a large size and wide viewing angle contains terabytes of data, urging the need for holographic data coding algorithms. In this paper, we propose a data coding algorithm suitable to the compression of holograms containing several billions of pixels. In our proposed approach, each holographic frame is subdivided into pixel blocks which are 2D Fourier transformed. The pixels thus obtained are rearranged to form new complex-valued segments whose amplitudes have characteristics close to orthographic projection images. These segments are ordered in sequence and their real and imaginary parts are encoded using the High-Efficiency Video Coding (HEVC) Main 4:4:4 coding profile with 4:0:0 chroma sampling.